PROFITABILITAS TERHADAP RETURN SAHAM - Happy Sista Devy (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2018)
The development of the capital market is currently followed by the development of the stock market is increasingly in demand by investors as well, seen from data on Indonesia Stock Exchange (IDX) which shows that the stocks included in the sharia has increased. An investor will do the analysis to make an investment decision. The analysis is technical and fundamental. One of the fundamental analysis is profitability ratio analysis issued by the company. Good financial performance will be the information used as a positive signal by investors, because companies that have good financial performance will provide more benefits for investors. The purpose of this research is to examine and analyze profitability variables on stock returns in Jakarta Islamic Index (JII) period 2012-2016. Population of this research is a company included in the Jakarta Islamic Index (JII). This research using sample criteria, we obtained a sample of 21 companies included in the Jakarta Islamic Index (JII) for the period of 2012-2016 and published annual financial report data on Indonesia Stock Exchange (IDX) required during the study. The variables used in this research are earning per share (EPS), return on equity (ROE), return on asset (ROA), return on sales (ROS), return on investment (ROI), size as control variable, and stock return as the dependent variable. Result of this research show that investor on Jakarta Islamic Index (JII) see simultaneously the profitability ratio as a signal for investment decision making. Variable size can be used as control variable in that used in this research. Profitability ratios that are taken by investors are return on assets (ROA), earnings per share (EPS), and return on investment (ROI). So that should be a special attention for companies incorporated in the Jakarta Islamic Index (JII) to increase investor interest to invest in the company. Keywords : stock return, profitability ratio, size.